DAMPAK COVID-19 TERHADAP ABNORMAL RETURN DAN VOLUME PERDAGANGAN SAHAM - Elvina Cahya Suryadi; Nungky Viana Feranita (STIE Mandala Jember, 2022)
The COVID-19 pandemic is a non-natural disaster that has a huge impact around the world. This research is a quantitative research with event study method. The purpose of this research is to test the capital market reaction by looking at abnormal returns and trading volume activity before and after the COVID-19 non-natural disaster. The event day in this study was April 13rd, 2020 when the Presidential Decree was issued regarding the designation of COVID-19 as a national disaster. Using purposive sampling method, the sample of this study were 27 companies engaged in the hotel, restaurant, and tourism sub-sectors listed on the Indonesia Stock Exchange. The event period is 11 days, namely 5 days before the event, 1 day at the time of the event and 5 days after the event. Data analysis using t-test and wilxocon signed ranks test. The results of this study are: 1) there is no abnormal return during the event period, 2) there is no difference in the average abnormal return before and after the COVID-19 non-natural disaster event, 3) there is no difference in the average trading volume activity before and after the COVID-19 non-natural disaster event and after the COVID-19 non-natural disaster event. Keywords: Event Study, Abnormal Return, Trading Volume Activity, COVID-19.